2010
DOI: 10.1136/bcr.04.2009.1782
|View full text |Cite
|
Sign up to set email alerts
|

Primary signet ring cell carcinoma of gall bladder: report of an extremely rare histological type of primary gall bladder carcinoma

Abstract: SummarySignet ring cell carcinoma is an extremely rare type of gall bladder carcinoma composed overwhelmingly (90%) of signet ring cells. It is necessary to exclude a gastric or colonic signet ring cell carcinoma secondarily involving the gall bladder. The primary aim of this case report is to describe the histopathological aspects of this tumour. Primary signet ring cell carcinoma of gall bladder shows dysplastic surface gall bladder epithelium with infiltration of gall bladder wall. It is also necessary to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 8 publications
1
3
0
Order By: Relevance
“…In addition, the tumor grossly resembled linitis plastica and no discrete mass was noted. This was comparable to the reports by Agarwal et al [4], Czyszczon and Alatassi [13], Ahmad and Qureshi [16], and Padhiari et al [17]. On the other hand, many reported cases presented as discrete masses in a background of diffuse or focal wall thickening [9,11,14,18].…”
Section: Discussionsupporting
confidence: 87%
“…In addition, the tumor grossly resembled linitis plastica and no discrete mass was noted. This was comparable to the reports by Agarwal et al [4], Czyszczon and Alatassi [13], Ahmad and Qureshi [16], and Padhiari et al [17]. On the other hand, many reported cases presented as discrete masses in a background of diffuse or focal wall thickening [9,11,14,18].…”
Section: Discussionsupporting
confidence: 87%
“…However, our case showed CK20, CDX-2, and MUC2 positivity in an immunohistochemical study. It has been reported that mucinous carcinomas, including signet ring cell carcinomas, often express the intestinal phenotype and/or the mixedmucinous phenotype [9,20]. We are not sure whether these phenotypes are related to the biological features such as prognosis or chemosensitivity.…”
Section: Discussionmentioning
confidence: 93%
“…A previous case report indicated that the features of signet ring cell carcinoma include linitis plastica-like invasion and poor prognosis [15] , [16] , [17] , [18] , [19] . In the present case, circumferential invasion of the gallbladder wall spreading along biliary tract suggested a signet ring cell component of MC.…”
Section: Discussionmentioning
confidence: 99%